1999
DOI: 10.1103/physrevlett.82.791
|View full text |Cite
|
Sign up to set email alerts
|

Step-Induced Optical Anisotropy of Vicinal Si(001)

Abstract: It is demonstrated, using reflectance difference spectroscopy, scanning tunneling microscopy, and low-energy electron diffraction, combined with deliberate straining of the surface, that the presence of atomic steps dramatically changes the optical anisotropy of the Si(001) surface. The step-induced reflectance difference signal originates predominately from rebonded steps and is comparable in magnitude to that of the terrace signal. [S0031-9007(98)08282-9]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
77
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 19 publications
13
77
0
Order By: Relevance
“…Figure 1 displays the real part spectra of the RA obtained on clean nominal and vicinal Si(001) surfaces. The RAS for vicinal surface is similar to the numerous previous results [5,16,23]. In the case of the nominal surface, our RA spectrum (a) is also identical to the previous results obtained by two groups [16,23].…”
Section: Ras Resultssupporting
confidence: 90%
“…Figure 1 displays the real part spectra of the RA obtained on clean nominal and vicinal Si(001) surfaces. The RAS for vicinal surface is similar to the numerous previous results [5,16,23]. In the case of the nominal surface, our RA spectrum (a) is also identical to the previous results obtained by two groups [16,23].…”
Section: Ras Resultssupporting
confidence: 90%
“…Shioda and van der Weide 17 found a similar behavior by decreasing the miscut angle of the vicinal surfaces, which corresponds to reducing the majority domain coverage (or, in other words, the anisotropy of the surface) . Yasuda et al 28 , from the analysis of their RT spectra, concluded that this peak is essentially originated by a step induced dicroism; however, the opposite conclusion has been reached by Jaloviar et al 34 , who singled out the contribution of the steps to the RA. In our spectra a peak in the energy region around 4.3 eV is present for the p(2 × 2) and c(4x2) reconstructions, in agreement with the observed reduction with increasing temperature.…”
mentioning
confidence: 94%
“…The agreement between the theoretical spectra obtained with the TB scheme and those computed within the DFT-LDA is not always satisfactory, confirming that the study of the optical properties of this surface is not a simple matter. From the experimental point of view, Shioda and van der Weide 17 and Jaloviar et al 34 pointed out recently the importance of a correct preparation of the clean surface (a terrace width about 1000 times larger than that obtained on vicinal surfaces, typically of 40-160Å, can be obtained with the techniques employed in Refs. 17 and 34) in order to minimize spurious effects due to the steps.…”
mentioning
confidence: 99%
“…2 and 3 as shown for Si(100). 20,21 The occurrence of minority domain terraces on the Geð100Þ: As ? sample is consistent with mutually perpendicular As dimers but also with selective As desorption revealing the underlying Ge dimers.…”
Section: -mentioning
confidence: 99%
“…20,21 On vicinal (100) surfaces, step-related RAS contributions depend on the step density, 21 and the atomic configuration of the steps. 20 According to Ref.…”
mentioning
confidence: 99%